The use of mobile phones and the heterogeneity of banana farmers in Rwanda - Kabirigi, M.; Sekabira, H.; Sun, Z.; Hermans, F. (Springer, 2023)
Information and communications technologies (ICTs) play a key role in improving agricultural production, enhancing socio-ecological resilience, and mitigating rural poverty. However, the use of ICTs for agricultural development among smallholder farmers, especially in the least developed countries, still lags behind. It is therefore critical to understand distinct attitudes among heterogeneous smallholder farmers that determine use of ICTs, such as mobile phones. Moreover, data-driven empirical studies on the use of mobile phones in smallholder settings are still scarce. We bridge this knowledge gap by evaluating the link between the use of mobile phones and various farming types of smallholder farmers in Rwanda. Using the principal component and cluster analysis, we analyzed 690 banana farming households across eight of the 10 major agro-ecological zones of Rwanda and developed a typology of banana farms. We identified three distinct farm types based on a combination of various farmer characteristics and farm operations and endowments, namely the beer banana, livestock-based, and the cooking banana farm types. These farm types clearly differ in terms of ownership and use of both basic and smart mobile devices. Farmers in the cooking banana farm type are far more likely to own and use smart mobile phones than in other types. Regression results further indicated that farm type, gender, and education have significant correlations with the perceived usefulness of mobile phones in agriculture. Major barriers to using ICT-based agricultural services were 1) low awareness of the existence of ICT services, 2) limited availability of ICT services, 3) lack of technical know-how, 4) relatively high prices of ICT devices, and 5) low levels of ICT literacy. This empirical study provides strategically important insights for the transition to digital agriculture in the context of smallholder farming systems.